A new species of Isopsestis (Lepidoptera: Thyatiridae) from Yunnan, China - Zhuang, Hailing; Owada, Mamoru; Wang, Min (Zootaxa, 2015)
A new species of genus Isopsestis Werny, 1968 (Lepidoptera: Thyatiridae), Isopsestis poculiformis sp. nov., is described from the locality 2660m elevation in Northeast Yunnan, China, and compared with its closest ally. Male adult and genitalia of the new species are illustrated and a distribution map of the genus Isopsestis Werny, 1968 is provided.